TINDAK TUTUR ILOKUSI DEKLARASI PADA KARAKTER HIBIKI DALAM FILM HIBIKI: SHOUSETSUKA NI NARU HOUHOU - Bunga Istni Mutiara Wardhani Ainur Rofiq Hidayat; Idah Hamidah; Hartati (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2025)
This article discusses the forms and functions of declarative illocutionary acts performed by the character Hibiki in the film HIBIKI: Shousetsuka ni Naru Houhou. This study employs a descriptive qualitative method with a pragmatic approach. Data were collected using observation and note-taking techniques, then analyzed using speech act theory by J.L. Austin and Searle, supported by local theories from Usami Mayumi (2002) and Kindaichi Haruhiko (1957). The results show that the character Hibiki uses declarative speech acts both directly and indirectly, not only in formal contexts but also in informal situations with social impact. The sub-function of Statements was found to be the most dominant, followed by Declaration of Intention and Ultimatum. This study reveals that illocutionary force in Japanese culture can be effectively conveyed through implicit speech forms, as long as they are supported by social context and the speaker’s position. Keywords: speech act, declaration, illocution, Japanese film, pragmatics, Hibiki